EPISTEMOLOGICAL FOUNDATIONS OF ISLAMIC EDUCATION CURRICULUM IN THE HADITH OF AT-TIRMIDHI AND AD-DARIMI - Almuzakky, Alamul Huda (Prodi Magister Pendidikan Agama Islam (MPAI) - STAI Nida El-Adabi Bogor, 2026)
The curriculum is a number of subjects taken by students in an educational institution, and in a broad sense the curriculum is